Unique benign soft tissue tumor suspected pyogenic granuloma in a young female hard palate: a case report - Epsilawati, Lusi; Azhari, Azhari; Yuza, Abel Tasman; Romdlon, Mahindra Awwaludin (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: This case aims to report the finding of a unique lesion in the maxilla in a young female patient. Case Report: The patient, a 21-year-old female, presented with a painless swelling on the left palate for the past 3 months, causing discomfort during eating. On intra-oral examination, there was visible swelling in the left hard palate area, extending from teeth 23 to 26 and extending to the middle of the palate. The patient was referred for a CBCT examination. The aim of writing this article is to assess the findings of a unique case of benign tumor of the palate. The results of the CBCT examination showed radiolucent lesions in the palatal mucosal area without bone resorption. The density of the lesion was higher than that of the surrounding mucosa. The lesion does not damage the tissue of the surrounding area. This is unique because swelling of this size is usually accompanied by extensive bone resorption. Based on its nature, this lesion was diagnosed as a benign soft tissue tumor with differential diagnoses of pyogenic granuloma, pleomorphic adenoma, leiomyoma, and desmoplastic fibroma. Conclusion: The lesion found was a soft tissue tumor lesion at the time; it was found to have a non-aggressive and non-expansive nature, making it difficult to determine a specific radiodiagnosis. The differential diagnosis of this case has been established as follows: Pleomorphic adenoma, pyogenic granuloma and leiomyoma, and pyogenic granuloma, were the options for establishing a provisional radiodiagnosis.